Animal abuse: beyond companion animals and domestic households - Wong, Rebecca W. Y. (Animal abuse and interpersonal violence, 2024)
It is easy to assume that animal abuse only involves the mistreatment of companion animals in a domestic setting, but animal abuse occurs in many forms and contexts. This chapter moves beyond the domestic household to address the problem of animal exploitation in two specific contexts: unregulated mercy release of aquatic species and poaching of protected species. The chapter also reflects on speciesism, which positions human beings as the most significant species resulting in the discrimination and ill-treatment of nonhuman species. It concludes that changes in human behavior and attitudes are essential to improve the treatment and welfare of nonhuman beings.